Algebraic graph theory : morphisms, monoids and matrices - Knauer, Ulrich, 1942-; Knauer, Kolja (De Gruyter, 2019)
The series is devoted to the publication of monographs and high-level textbooks in mathematics, mathematical methods and their applications. Apart from covering important areas of current interest, a major aim is to make topics of an interdisciplinary nature accessible to the non-specialist. The works in this series are addressed to advanced students and researchers in mathematics and theoretical physics. In addition, it can serve as a guide for lectures and seminars on a graduate level. The series de Gruyter Studies in Mathematics was founded ca. 30 years ago by the late Professor Heinz Bauer.- Resumé vydavatel
Keywords: teorie grafů; algebraická teorie grafů; algebraická topologie; graph theory; algebraic graph theory; algebraic topology; elektronické knihy; monografie; electronic books; monographs